2018
DOI: 10.3390/ijerph15112607
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetes Mellitus among Roma Populations—A Systematic Review

Abstract: Background: The aim of this study was to estimate the prevalence of diabetes mellitus in the Roma population and compare it to the prevalence in the Caucasian population. Methods: Using the words “Roma”, “Gypsies”, “Romani”, and ”traveler” in combination with “diabetes, “metabolic syndrome”, “cardiovascular disease” and “health status” we searched the MEDLINE, Pubmed and Scopus databases for articles in English that focused on the prevalence of diabetes mellitus among Roma populations published until December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 47 publications
(57 reference statements)
0
17
0
Order By: Relevance
“…It has been thoroughly demonstrated that Roma people are overrepresented in marginalized communities and live in unhealthy environments, and their health behaviour is significantly less favourable than that of the non-Roma population [ 38 , 64 , 65 , 66 ]. The health of Roma can be considered as global ill health [ 1 ], based not only on the burden of rare and infectious diseases [ 4 , 5 ], but also on chronic non-communicable diseases of high public health importance, such as cardiometabolic diseases, which are significantly higher among them than in the majority population [ 7 , 8 , 9 , 11 , 12 , 13 , 67 ]. In addition, the access of Roma people to health care is also impaired, resulting in a broad spectrum of unmet health needs [ 68 , 69 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been thoroughly demonstrated that Roma people are overrepresented in marginalized communities and live in unhealthy environments, and their health behaviour is significantly less favourable than that of the non-Roma population [ 38 , 64 , 65 , 66 ]. The health of Roma can be considered as global ill health [ 1 ], based not only on the burden of rare and infectious diseases [ 4 , 5 ], but also on chronic non-communicable diseases of high public health importance, such as cardiometabolic diseases, which are significantly higher among them than in the majority population [ 7 , 8 , 9 , 11 , 12 , 13 , 67 ]. In addition, the access of Roma people to health care is also impaired, resulting in a broad spectrum of unmet health needs [ 68 , 69 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, common study limitations include a low number of participants and the absence of a majority population group as a reference. For example, the latest literature review on the prevalence of diabetes mellitus among Roma notes that altogether, four previously published papers suggested a higher prevalence of diabetes among Roma than in Caucasians, and “none of them reached the standards regarding representative samples and number of cases for a conclusive result” [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, the higher prevalence of T2DM among Roma in Slovakia, Serbia, and Hungary compared to the general population (of Caucasian origin) was also demonstrated [12,13,14,15,16,17]. Although the latest review of the published literature [18] concludes that studies on T2DM prevalence are insufficient in design, and none of them reach the necessary standards regarding representative samples and number of participants, the authors raise a possible genetic risk to T2DM among Roma known to have Asian origin by accepting the theory of the increased genetic susceptibility to T2DM in different (Japanese, Chinese, and Indian) Asian populations [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Historical migration has led to their dispersion over many European countries [ 4 , 5 , 6 ] and they have been subjected to disadvantaged living conditions, food insecurity, high-risk health-related behaviors, as well as discrimination, stigmatization and barriers to accessing health services [ 7 , 8 , 9 , 10 , 11 ]. These exposures have resulted in a particularly poor health status indicated by the high prevalence of chronic morbidity, particularly diet-related non-communicable diseases (NCDs) [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ], as well as an estimated life expectancy of almost a decade less, compared to the general population in Europe [ 16 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%